2020
DOI: 10.1007/s42464-020-00063-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-rubber components on the branching structure and the accelerated storage hardening in Hevea rubber

Abstract: Natural rubber (NR) contains cis-1,4-polyisoprene as well as a small quantity of non-rubber components, affecting the physical properties of NR, especially the storage hardening via gel formation. The free and/or linked non-rubber components were removed from NR by various treatments. The origin of gel formation in NR mainly resulted from proteins, which could be removed by enzymatic deproteinisation, surfactant washing or saponification treatment, and partly from phospholipids linked to NR molecule via H-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(69 reference statements)
0
9
0
1
Order By: Relevance
“…Deproteinized NR (DPNR) latex was prepared by incubating 30% DRC of FL‐latex with 0.04% wt/vol proteolytic enzyme (Kao KP‐3939) in the presence of 1% wt/vol sodium dodecyl sulphate (SDS) at 37°C for 16 h, [ 17 ] followed by washing twice by centrifugation at 12,000 rpm for 30 min. DPNR film was cast on a clean petri dish and dried at RT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deproteinized NR (DPNR) latex was prepared by incubating 30% DRC of FL‐latex with 0.04% wt/vol proteolytic enzyme (Kao KP‐3939) in the presence of 1% wt/vol sodium dodecyl sulphate (SDS) at 37°C for 16 h, [ 17 ] followed by washing twice by centrifugation at 12,000 rpm for 30 min. DPNR film was cast on a clean petri dish and dried at RT.…”
Section: Methodsmentioning
confidence: 99%
“…[ 15 ] Besides using thiol compound as bleaching agent, it was found that soaking of coagulated NR in hot water could reduce the color as well as the total phenolic content in NR. [ 16 ] Purifications by deproteinization [ 17 ] and transesterification [ 18 ] are methods for removing proteins and lipids from NR latex/solution, respectively, that will reduce coloring substances present in NR. Vulcanized NR prepared from highly purified rubber by saponification was light‐yellow in color.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the natural rubber was numerous properties such as high tensile and tear strengths, low heat build-up, good processability, etc. Moreover, the natural rubber can be applied for many products such as pillow, gloves, flexible films and car tires [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The research studies show that the non-rubber components in NR are connected with main chain through α-terminal, ω-terminal, and metal ions to form network structure [12][13][14][15]. For instance, Sakdapipanich et al verified the existence of the non-rubber components in the natural network based on the crystallization behaviors.…”
Section: Introductionmentioning
confidence: 99%